2018
DOI: 10.1017/s0266467418000275
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effect of typhoons on vascular epiphytes in Taiwan

Abstract: Abstract:We used all 167 typhoon warnings issued by the Taiwanese Central Weather Bureau from 1958–2006 to assess the long-term effect of cyclone disturbance on vascular epiphytes. Tracks and eyes of past typhoons were plotted as circles with radii of Beaufort scale 7 and 10, and the frequency of each cohort in 1-km2 grid cells was calculated. The presence of vascular epiphytes in the same grid cells was predicted using species distribution models (SDMs). First, we used herbarium specimens and other sources to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Similar climate-driven shifts in community composition have been reported for forest trees, as well as for plant communities in other ecosystems (Feeley et al 2020). Future models should incorporate the effects of increased extreme weather events and variability (e.g., Hsu et al 2018;Kennard et al 2020) and potential positive feedback from climate-induced overstory decline (e.g., Zellweger et al 2020), as well as more information on intraspecific variation in traits (e.g., specific leaf area) that could contribute to the adaptation of herbaceous plant communities to global change (Blondeel et al 2020).…”
Section: Introductionsupporting
confidence: 54%
“…Similar climate-driven shifts in community composition have been reported for forest trees, as well as for plant communities in other ecosystems (Feeley et al 2020). Future models should incorporate the effects of increased extreme weather events and variability (e.g., Hsu et al 2018;Kennard et al 2020) and potential positive feedback from climate-induced overstory decline (e.g., Zellweger et al 2020), as well as more information on intraspecific variation in traits (e.g., specific leaf area) that could contribute to the adaptation of herbaceous plant communities to global change (Blondeel et al 2020).…”
Section: Introductionsupporting
confidence: 54%
“…In most cases, the effects of hurricanes negatively affected EM. For example, following hurricanes in Mexico, Honduras, and Taiwan, epiphyte abundance and diversity were significantly reduced in dry and wet temperate and tropical forests (Goode & Allen, 2008; Batke & Kelly, 2015; Hsu et al ., 2018; Novais et al ., 2020). Extreme wind events also reduced the height location within trees in Honduras (Batke & Kelly, 2015), and fire in Florida (Robertson & Platt, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Waide & Kingsland, 2021), but are critical to understand disturbance effects on slow-growing species such as epiphytic shrubs and their host trees. The use of modeling approach have expanded these scales; for example, Hsu et al (2018) suggested that by 2100, the majority of epiphyte species were projected to lose 45-60% of their current range, shifting to higher elevation areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation